Factor Affecting Customers’ Acceptance of Self-service Restaurant Ordering System (SROS) in Johor Restaurant - Lim Jie Yee,; Chan, Shiau Wei; Fadillah Ismail,; Md Fauzi Ahmad,; Rumaizah Ruslan,; Rohaizan Ramlan,; Nur Syereena Nojumuddin,; Izzuddin Zaman, (Research in Management of Technology and Business, 2024)
The advancement of technology has led the restaurant sector towards a sustainable future where a self-service restaurant ordering system (SROS) can be utilized at every level of the service process. However, customers who had used the SROS at McDonald’s and Haidilao Hot Pot found that SROS such as the older generation didn’t want to learn or relearn due to age because they think this technology is complicated and too much hassle and the young generation also has internet problems. Moreover, customers of McDonald's and Haidilao Hot Pot found that the inevitability of any technology is that at some point it will need downtime for maintenance. Hence, this research aimed to measure the level of SROS received expected by customers and identify the determinants influencing customers’ intention to use SROS in Johor restaurants. 384 customers who had used the SROS at McDonald's and Haidilao Hot Pot were involved in this study. A survey questionnaire was distributed online survey to the respondents to collect the data. The data collected were analyzed quantitatively by using SPSS. The result showed that customers had a high level of SROS as well as performance expectancy, effort expectancy, social influence, and facilitating conditions are significantly correlated intention with to use. This study will provide deeper insights that will increase customers’ intention to use SROS. Besides, this study can help restaurant practitioners to analyze the factors considered by customers regarding these technologies.